Drug Utilization Study of Antibiotics in Bacterial Meningitis (A Retrospective Study in Dr. Soetomo General Hospital, Surabaya, Indonesia) - Andarsari, Mareta Rindang; Hasmono, Didik; Samirah, Samirah; Suharjono, Suharjono; Nabilah, Dea Ayu; Sugianto, Paulus (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2019)
Background: Meningitis defined as an inflammation of the meninges, a membrane that surrounds the brain. The inflammation is a result from bacterial infection. Central nervous system infection is a medical emergency because of the progressivity and potentially life-threatening. Antibiotics usage become crucial to reduce morbidity and mortality. Objective: This study was aimed to assess the use of antibiotics, prescribed for patients with bacterial meningitis in Neurology Department of Dr. Soetomo General Hospital Surabaya from January 2010 until June 2015. Methods: Retrospective study using medical record of inpatients obtained from January 1st 2010 until June 30th 2015. The inclusion criteria were inpatients with bacterial meningitis (diagnosed by physician using CT scan data, lumbal puncture and clinical signs and symptoms) and prescribed with antibiotics. Patients with antibiotics therapy less than 3 days and infection other than bacterials were excluded. Results: From 85 patients, male to female ratio was 1.66. Meningitis appear to be mostly occured in productive age, 39 (45.88%) in 15 - 29 years old and 40 (47.06%) in 30 - 60 years old. Number of antibiotics prescribed were 130 prescriptions, as single and combination therapy. The most prescribed antibiotic was cephalosporins (97 prescriptions), dominated by 2 g twice daily ceftriaxone with 86 (66.15%) from overall prescriptions. Followed by metronidazole and fluoroquinolons,11 (8.46%) and 8 (6.15%) respectively. In addition, there were 26 prescriptions of combination therapy, mostly ceftriaxone and metronidazole. Conclusion: Bacterial meningitis are mostly treated using ceftriaxone which is an appropriate drug of choice.